Map compiling, map reading, and cartographic design in "Pragmatic pyramid of thematic mapping" - Medyńska-Gulij, Beata (Quaestiones Geographicae, 2010)
This paper concerns the dependent relationships between map compilation, map reading, and cartographic design with special regard to thematic mapping. The first step is to measure the simple relationship between cartographic practice and map design and present a pyramid of pragmatic thematic mapping. The model contains various types of maps, a range of cartographic principles, and sources of knowledge for map design. When presented as a pyramid, these functional dependencies can refer to a series of pragmatic criteria which relate to the use of thematic maps.